‘Promotion of Mental Health and Prevention of Suicide’: Theme of World Mental Health Day 2019 - Ahmed, Ahsan Uddin (Journal of Shaheed Suhrawardy Medical College, 2020)
Abstract not available J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 84-85